Predicting Nipple Necrosis with a “Lights-on” Indocyanine Green Imaging System: A Report of Two Patients - Shaffrey, Ellen C.; Moura, Steven P.; Jupitz, Sydney; Seets, Trevor; Kawahara, Tisha; Uselmann, Adam; Lin, Christie; Poore, Samuel O. (Archives of Plastic Surgery, 2024)
Nipple–areolar complex (NAC) necrosis is a devastating complication in nipple-sparing mastectomies (NSMs) that significantly impacts patient's quality of life. The use of fluorescence angiography for intraoperative assessment of mastectomy skin flap perfusion in NSM has been successfully described and can be utilized to help guide surgical decision-making. Recently, a novel fluorescence-guided surgical imager was developed, OnLume Avata System (OnLume Surgical, Madison, WI), which provides intraoperative evaluation of vascular perfusion in ambient light. In this case report, we describe the use of OnLume fluorescence-guided surgery technology to help aid in clinical decision-making for two breast reconstruction cases with concern for intraoperative nipple hypoperfusion.
Keywords: fluorescence imaging; intraoperative; ambient light compatible; breast reconstruction; nipple necrosis